2019
DOI: 10.17159/2309-8309/2019/v18n3a2
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients with Blount's disease at an academic hospital

Abstract: Background: Despite an apparent increased burden of Blount's disease in South Africa, little is known of its epidemiology and associated features. The aim of this study is to explore the profile of South African patients with Blount's disease seen at an academic hospital, with respect to family history, ethnicity, associated milestones, sex, bilateral involvement and obesity. Methods: We retrospectively evaluated the hospital records of children diagnosed with Blount's disease (infantile, juvenile and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…The present study found a higher prevalence of females among children with ITV (69%), as previously reported by many authors [8,[21][22][23]. Of note is the influence of sex on surgical outcome.…”
Section: Discussionsupporting
confidence: 89%
“…The present study found a higher prevalence of females among children with ITV (69%), as previously reported by many authors [8,[21][22][23]. Of note is the influence of sex on surgical outcome.…”
Section: Discussionsupporting
confidence: 89%
“…20 More recently, Mehtar et al confirmed this finding in a cohort of 108 children with Blount's disease from the same area (Johannesburg, South Africa). 21 Vitamin D plays multiple roles in the musculoskeletal system, and its association with Blount's disease has been investigated. One study in a cohort of patients attending an obesity clinic found 12 children with Blount's disease, and an association with low levels of vitamin D. 22 This finding was referenced in recent literature reviews.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…26 Mehtar et al confirmed these findings with 82% being female and 64% having bilateral disease from a cohort of 108 children with Blount's disease (44 with IBD). 21 Measuring and plotting the BMI percentile for age and sex is essential to identify children at risk for obesity and to initiate early intervention.…”
Section: Patient Profilementioning
confidence: 99%